The essence - Derting, Kimberly (Derting, Kimberly. Pledge novel., 2013)
Seventeen-year-old Charlaina "Charlie" Hart has defeated the tyrant Queen Sabara and taken control of Ludania, only to have Sabara's soul fuse itself with her own.